Impact of Perceived Servicescape on Patient Satisfaction through Mediating Role of Service Credibility and Moderating Role of Received Word of Mouth in Rehabilitation - Zahid, Tanzila (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The aim of this study was to explore the effects of perceived servicescape (PS) and credibility of the healthcare service provider (CHSP) on patient satisfaction(PtS) in rehabilitation settings of public and private hospitals of Islamabad and Rawalpindi, Pakistan. Mediating effect of CHSP and moderating effect of received word of mouth (WOM) have also been studied in this relationship. A sample of 300 patients receiving rehabilitation care was selected by applying convenience sampling technique. The design of this study was cross-sectional in nature. Self-administered questionnaire was designed to be utilized. Application of the correlation and regression were executed to analyze the collected quantitative data. The cross-sectional study method, limited geographical area coverage, and small sample size did not allow the detailed testing of the causal relations among study variables. Results of this study have indicated that there was a significant direct positive relationship between perceived servicescape and patient satisfaction and this relationship was also mediated positively by CHSP. There was a substantial direct positive relationship between perceived servicescape and CHSP and, between CHSP and patient satisfaction. However, the moderating effect of received WOM was found to be insignificant. It is recommended that healthcare managers should develop a credible service framework that focuses on better affordability, competitiveness, awareness, empathy, service expertise, pleasant interactions with patients through centeredness communication and beliefs and, subsequently, it will contribute to patient satisfaction and success of the rehabilitation settings. This is the first-ever study of the impact of perceived servicescape on patient satisfaction through CHSP as a mediator and the moderating influence of received WOM in rehabilitation.